Portrayal of Violence in Morrison’s A Mercy - Salma Naz; Ghazal Shaikh (University of Chitral Journal of Linguistics and Literature, 2024)
This research paper examines the portrayal of violence in Morrison’s novel A Mercy through textual analysis. This analysis is done through the lens of Žižek's theory of violence: subjective and objective. Subjective violence includes the concepts of physical violence and terror, while objective violence deals with invisible violence like structural inequality in the form of systemic violence. Morrison’s novel goes beyond subjective physical violence. It is found that A Mercy reveals Žižek's subjective violence in two ways. First, women are dominated through subjective physical violence. Second, they suffer from subjective sexual violence, too. Likewise, objective violence is depicted through systemic and symbolic violence. Systemic refers to the structural inequalities inherent in the structure through the domination and discrimination of men over women and the inferior attitude of women towards other women. Symbolic violence is portrayed through men's use of the language of discrimination and domination to control women.Additionally, this paper addresses how women do violence against other women. Related to the impact of violence, the researchers found that the effects of violence on women's self-identity based on race and gender are shattered. They impose violence on their female community and question their own identities. Violence results in breaking the interpersonal relationships of characters, too. Objective violence (domination and discrimination) breaks the family unit and shakes the trust of family members against one another. However, not all characters passively accept the impact of violence; some female characters resist it too, and they reclaim their own identities.